Effect of Hypercholesterolemia on Experimental Colonic Anastomonic Wound Healing in Rats - Sen, Meral; Anadol, A. Ziya; Oguz, Mehmet (Baishideng Publishing Group Co, 2006)
Aim: To evaluate the mechanical and biochemical parameters of colonic anastomotic healing in hypercholesterolemic rats. Methods: Sixty rats were divided into two groups of 30 each according to their dietary regimens. The test group was fed with a high cholesterol-containing diet for two months while the control group had standard diet. These two groups were further divided into three subgroups consisting of ten rats each. After hypercholesterolemia was established, left colon resection and anastomosis were performed in both groups and samples from liver and abdominal aorta were taken to evaluate the systemic effects of hypercholesterolemia. Anastomotic wound healing, blow-out pressures and tissue hydroxyproline levels were evaluated. Results: The test group had a significant weight gain in two months. Microscopic examination of the abdominal aorta revealed no atherosclerotic change in none of the groups, but liver tissue specimens showed significant steatosis in the test group. Tissue hydroxyproline levels and anastornotic blow-out pressures were significantly lower in the test group than in the controls. Conlusion: Hypercholesterolemia not only increases hydroxyproline levels and blow-out ressures but also worsens anastomotic wound healing. © 2006 The WJG Press. All rights reserved.
Keywords: Anastomic Wound Healing; Colonic Anastomosis; Hypercholesterolemia